(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed at identifying the role of the school as a reform tool from the point of view of parents at Hebron Governorate. The study sample consisted of (280 parents ) at Hebron Governorate, who were chosen by random method. It was found that the role of the school as a reform tool came to a high degree, and the results of the study concluded that there were no statistically significant differences attributed to the study variables (gender, educational qualification). Through the results of the current study , the researcher recommended the following : 1-The necessity of activating the mechanisms of communication with parents through preparing annual plans and through permanent meetings with them .